1990
DOI: 10.1111/j.1574-6968.1990.tb03797.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression of outer-membrane proteins in Neisseria meningitidis in iron-replete and iron-deficient media

Abstract: A total of 103 Neisseria strains, including 42 carrier and 40 invasive N. meningitidis and 21 commensal species were studied. Outer‐membrane proteins from carrier and invasive N. meningitidis showed similar molecular mass distributions (except in the range from 78 to 82 kDa in which 90% of the invasive but only 47.6% of the carrier strains expressed proteins), many strains showin neither class II (41 kDa) nor class III (38 kDa) proteins. When grown in iron‐restricted conditions proteins were induced mainly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The cells grown under iron-restricted conditions (of all serogroups and serotypes examined) bind 2-to 35-fold more gold-labelled HTF than do cells grown under iron-sufficient conditions, indicating the increased expression of HTF receptor activity under such stress. The findings of increased expression of the HTF receptor under iron limitation are in general agreement with results obtained from studies on whole cells and from Western blot analysis of OMPs of N. meningitidis grown under different conditions (1,8,9,13,17). In contrast, these findings do not agree with those reported by Simonson et al (14), who concluded that iron-replete and iron-restricted cells bind approximately the same number of HTF molecules.…”
Section: Discussionsupporting
confidence: 81%
“…The cells grown under iron-restricted conditions (of all serogroups and serotypes examined) bind 2-to 35-fold more gold-labelled HTF than do cells grown under iron-sufficient conditions, indicating the increased expression of HTF receptor activity under such stress. The findings of increased expression of the HTF receptor under iron limitation are in general agreement with results obtained from studies on whole cells and from Western blot analysis of OMPs of N. meningitidis grown under different conditions (1,8,9,13,17). In contrast, these findings do not agree with those reported by Simonson et al (14), who concluded that iron-replete and iron-restricted cells bind approximately the same number of HTF molecules.…”
Section: Discussionsupporting
confidence: 81%
“…Excreted blebs and bacterial outer membranes were obtained as previously described [19] from cultures grown in MH or MH-EDDA for SDS-PAGE analysis, and only from those grown in MH-EDDA for TBP2 isolation. The cultures were centrifuged at 48 000 x g, the pellets being resuspended in 0.1 M acetate buffer-0.2 M lithium chloride (pH 5.8), with two 10-s ultrasonic pulses, incubated for 2 h at 45°C in a shaking water bath and passed through a 21-gauge needle.…”
Section: Extraction Of Ompsmentioning
confidence: 99%
“…The outer membrane composition of bacteria grown in normal culture media, in which iron is freely available, can be significantly different from that of invasive bacteria recovered directly from hosts, especially in the case of N. meningitidis. In particular, iron-regulated OMPs (IROMPs), some of which are involved in iron uptake mechanisms (26,27), are synthesized only under iron restriction (11,19) and later the antigenicity of the outer membrane of N. meningitidis (2-4, 15, 17).…”
mentioning
confidence: 99%